Effects of Virginia's 2019 Medicaid Expansion on Health Insurance Coverage, Access to Care, and Health Status - Wei Lyu PhD; George L. Wehby PhD (SAGE Publishing, 2022)
Virginia expanded Medicaid under the Affordable Care Act beginning in January 2019, which substantially increased income eligibility up to 138% of the federal poverty level (FPL) for both childless adults and parents. In this study, we examined the effects of Virginia's Medicaid expansion in 2019 on health insurance coverage, access to care, and health status by employing a difference-in-differences and a synthetic control design. The study included data on health insurance from the 2016-2020 American Community Survey (ACS) and data on access to care and health status come from the 2016-2020 Behavioral Risk Factors Surveillance System (BRFSS). The samples from ACS and BRFSS were limited to non-elderly adults with income below 138% of the FPL. Separate models were estimated for individuals below 100% of FPL, and those within 100-138% of FPL. The Virginia Medicaid expansion was associated with a 9-11 percentage-point increase in Medicaid coverage rate and a 7-8 percentage-point increase in the insured rate among individuals below 100% FPL, in the first two years of expansion. There was a larger increase in Medicaid coverage among individuals within 100-138% of FPL which also led to a larger increase in the insured rate in 2020. Both income groups showed no changes in private coverage after the expansion in Virginia. We also found a decline in delaying necessary medical visits due to cost for individuals below 100% FPL in 2019 and for individuals within 100-138% FPL in 2020. There was overall no discernable change in health status outcomes. Virginia's 2019 Medicaid expansion substantially increased insurance coverage among poor adults with suggestive early evidence for improved access. The findings highlight the missed opportunity for other states that have not yet decided to expand their Medicaid programs to improve coverage and access among their low-income individuals.